Synthesis and characterizations of bio-phenolic furfural resins via liquefaction and resinification of empty fruit bunch fibres - Noor Aina Suhaila, Anuar (2016)
In this study, Bio-Phenolic Furfural resins was synthesized from oil palm Empty Fruit Bunch (EFB) fibres via liquefaction process using phenol, sulphuric acid and phosphoric acid, followed by resinification reaction with furfural in alkaline condition. The method that has been used in this research was oil bath heating technique with time reaction of 120 minutes at temperature of 150 oC. The Fourier Transform Infrared (FTIR) analysis of Bio-Phenolic Furfural Resin for different type of catalyst shows that catalyst of sulphuric acid indicates the best IR spectra with strongest intensity of peak compared to resin that used catalyst ratio between sulphuric acid and phosphoric acid. This is because sulphuric acid showed its characteristics as strong acid. Next, for Thermogravimetric Analysis (TGA) result it shows that resin that involved two types of catalyst during the reaction, which are sulphuric acid and phosphoric acid could emerge as a product with high thermal stability. This is due to the temperature consumed by them is slower for the same major weight loss which was about 82.92 %, compared to the resin with catalyst of sulphuric acid. In conclusion, since the function of catalyst is to speed up the chemical reaction, both type of these acid that were act as catalyst in this research shows their own advantages and ability for the production of Bio-Phenolic Furfural Resin. Both of them are highly recommended for the production of this resin.